Một số công cụ hỗ trợ tự động hóa phân loại và biên mục tài liệu - Đinh, Thúy Quỳnh (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
The article introduces several e-tools to assist the information processing at libraries and information centres as well as to improve automatic library activities  performance